RESPONSABILIDADE SOCIAL, PREGAÇÃO E EDUCAÇÃO: TENSÕES MISSIOLÓGICAS NO PROJETO MISSIONÁRIO DA IGREJA METODISTA EM TERRAS BRASILEIRAS - Lopes, Nicanor (2012)
The aim of the present research, Social Responsibility, Preaching and Education: missiological tensions in the Missionary Project of the Methodist Church on Brazilian soil, is to examine the missionary action of the Methodist Church, since its implementation up to the period referring to the 18th General Conference (2006 2011). The study rescued that the triad of Social Responsibility, Preaching and Education represents a distinct identity of the Wesleyan Movement, and that such a missionary principle has not been closely followed by the Brazilian Methodism. It is noteworthy that the triad was especially significant in the missionary project, which is particularly noticeable during its implementation, as well as in the constitution of the so-called Plano para Vida e Missão (PVM). Once assumed that the missionary action in the Brazilian Methodism has not fully been characterized by systematic theological reflections, the triad of Social Responsibility, Preaching and Education has always played a prominent role in the mission. In many instances, a considerable strain was put on the Methodist missionary project. The intense focus on the number of followers and geographic expansion did not contribute to maintain great fidelity to the triad and its ideals. Along the way research is built in four chapters, in which one seeks refine a historical understanding of the process unfolded in this study, it is crucial that the essential regulatory framework of the triad as the Methodist mission. The research highlights the importance of further studies so that Methodism can take on a fundamental role in the Missio Dei, enlightened by the triad of Social Responsibility, Preaching and Education.